Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Motivasi dan Hasil Belajar Pada Materi Pencemaran dan Kerusakan Lingkungan Pada Kelas VII.1 di SMP Negeri 13 Pekanbaru - R. Rosyidah (Instructional Development Journal, 2018)
The background of this study is the low motivation and learning outcomes of class VII.1 SMP Negeri 13 Pekanbaru. This study aims to improve the motivation and learning outcomes of students of class VII.1 SMP Negeri 13 Pekanbaru through the application of the Jigsaw type cooperative learning model to the material of pollution and environmental damage. The study was conducted in 2 cycles and each cycle consisted of 2 meetings. The data obtained is in the form of final test data (post test) from each cycle, the results of observational data on affective aspects and the results of filling in the motivation questionnaire. Data analysis in this study was carried out qualitatively and quantitatively. Based on the research that has been done, it can be concluded that the application of the Jigsaw type cooperative learning method to class VII.1 students of SMP Negeri 13 Pekanbaru can increase motivation and learning outcomes in biological matter of pollution and environmental damage. Based on the analysis of research data, the acquisition of scores from questionnaires on student learning motivation was very high, from 63% to 84% in the very high category. Meanwhile for cognitive aspects of learning outcomes, the average score obtained in the first cycle was 68.75 with a percentage of KKM completeness of 37.50%, increasing to 83.78 with a percentage of KKM completeness of 80% in cycle II. Whereas for affective learning outcomes also in accordance with the expected target of achievement, namely an increase in the high category. Where in the first cycle, 83% of students were in the high category and 17% in the medium category, while in the second cycle, 100% of the students were in the high category.